2016
DOI: 10.2147/ijn.s102467
|View full text |Cite
|
Sign up to set email alerts
|

Chimeric HBcAg virus-like particles presenting a HPV 16 E7 epitope significantly suppressed tumor progression through preventive or therapeutic immunization in a TC-1-grafted mouse model

Abstract: Background Therapeutic human papillomavirus (HPV) vaccines are currently being developed. However, no therapeutic efficacy has been achieved in clinical trials for the treatment of cervical intraepithelial neoplasia or cancer. One of the important issues in increasing vaccine efficacy is determining the best way to enhance tumor antigen-specific cellular immune responses. This study aimed to explore the virus-like particles (VLPs) of hepatitis B core antigen (HBcAg) as potential therapeutic vaccin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 31 publications
(37 reference statements)
0
5
0
Order By: Relevance
“…While it would be intriguing to investigate the extend of HBcAg carrier-specific responses elicited by HBcAg-zDIII VLPs in the future, extensive studies have shown that carrier-specific antibody responses to HBcAg are often mild and do not have significant negative influences on the immunogenicity of the foreign epitopes displayed by HBcAg VLPs 34 , 35 . For example, carrier-specific anti-HBcAg antibodies were found to have minimal effect on the antigen presentation, the induction of antigen-specific antibody and cytotoxic T-cell responses, and the protective immunity of antigens that are displayed by HBcAg VLPs 34 36 . The induction of carrier-specific antibodies may also prevent the use of the vaccine in populations that have pre-exposure to hepatitis B virus.…”
Section: Discussionmentioning
confidence: 99%
“…While it would be intriguing to investigate the extend of HBcAg carrier-specific responses elicited by HBcAg-zDIII VLPs in the future, extensive studies have shown that carrier-specific antibody responses to HBcAg are often mild and do not have significant negative influences on the immunogenicity of the foreign epitopes displayed by HBcAg VLPs 34 , 35 . For example, carrier-specific anti-HBcAg antibodies were found to have minimal effect on the antigen presentation, the induction of antigen-specific antibody and cytotoxic T-cell responses, and the protective immunity of antigens that are displayed by HBcAg VLPs 34 36 . The induction of carrier-specific antibodies may also prevent the use of the vaccine in populations that have pre-exposure to hepatitis B virus.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the nanoscale structure of HBcAg can be more effectively identified and processed by APCs (Lee et al, 2009; Ong, Tan & Ho, 2017). Therefore, HBcAg has been used as an vaccine carrier for several exogenous pathogens (e.g., hepatitis B, C, and E virus, influenza virus, foot-and-mouth disease virus, Human enterovirus 71, coxsackievirus A16, and C. trachomatis ), and the immunogenicity of recombinant HBc-based VLP vaccines against pathogens has also been verified in animal models (Dai et al, 2016; Su et al, 2013; Zheng et al, 2016; Chu et al, 2016; Zhu et al, 2016; Wu et al, 2017; Jiang et al, 2017). VLPs are the self-assembled structural proteins of most viruses and can stimulate the immune response in the absence of an adjuvant by exposing pathogen epitopes and simulating the structure of natural viruses (Plummer & Manchester, 2011; Yang et al, 2016).…”
Section: Virus-like Particles As Built-in Adjuvant Platformsmentioning
confidence: 99%
“…In addition, the nanoscale structure of HBcAg can be more effectively identified and processed by APCs (Lee et al, 2009;Ong et al, 2017). Therefore, HBcAg has been used as an vaccine carrier for several exogenous pathogens (e.g., hepatitis B, C, and E virus, influenza virus, foot-and-mouth disease virus, Human enterovirus 71, coxsackievirus A16, and Chlamydia trachomatis), and the immunogenicity of recombinant HBc-based virus like particle (VLP) vaccines against pathogens has also been verified in animal models (Dai et al, 2016;Su et al, 2013;Zheng et al, 2016;Chu et al, 2016;Zhu et al, 2016;Wu et al, 2017;Jiang et al, 2017). VLPs are the self-assembled structural proteins of most viruses and can stimulate the immune response in the absence of an adjuvant by exposing pathogen epitopes and simulating the structure of natural viruses (Plummer & Manchester, 2011;Yang et al, 2016).…”
Section: Salmonella Porinmentioning
confidence: 99%